Training Science Process Skills with the SETS Model in Biotechnology Learning: Applications and Future Research Directions - Hasan Subekti; Sapti Puspitarini; Edi Suwandi (Postgraduate, University of Mataram, 2025)
The purpose of this study is to investigate how biotechnology education focuses on learning implementation, student activities, Science Process Skills (SPS), field constraints, student responses, and to identify future research directions. The study employs descriptive quantitative research involving students at the junior high school Unesa. The data is gathered through observation, test and questionnaire. The data are analysed descriptively. Based on what the observer thought, the data showed that learning went very well. It's mostly made up of talking between students and teachers, like asking questions and having conversations. At most, problem-solving and data collection skills were learned, but things like media, classroom, and time management were not. Student responses were positive to the SETS model, but their understanding of scientific work and evaluation questions needed to be improved. These potentially affect the priority research agenda, which focuses on technology integration, teacher training, contextual learning, interdisciplinary approaches, and the integrated biotechnology of SETS. The study concludes that SETS model learning was carried out very well and received a positive response from students, with active interaction between students and teachers, especially in verbal interaction and SPS, such as formulating problems and data collecting.